Synthesis of nitrogen doped faceted titanium dioxide in pure brookite phase with enhanced visible light photoactivity - Pan, J.; Jiang, San Ping (2016)
Brookite titanium dioxide (TiO2) is rarely studied, as compared with anatase and rutile phases TiO2, due to its comparatively lower photoactivity. It has been recently reported that brookite TiO2 with active facets exhibits excellent performance, however, synthesis of such faceted brookite TiO2 is difficult because of its low thermodynamic phase stability and low structural symmetric. Furthermore, like faceted anatase and rutile TiO2, faceted brookite TiO2 is not responsive to visible light due to its wide bandgap. In this study, a novel dopant, hydrazine, was introduced in the development of nitrogen doping. By applying this dopant, nitrogen doped brookite nanorods with active (120), (111) and (011) facets were successfully synthesized. The resultant materials exhibited remarkably enhanced visible-light photoactivity in photodegradation.